Clinical impact of systematic nutritional care in adults submitted to allogeneic hematopoietic stem cell transplantation - Sommacal, Heloisa Martins (Associação Brasileira de Hematologia e Hemoterapia, 2012)
BACKGROUND: The development of nutrition care programs for patients undergoing hematopoietic stem cell transplantation is necessity in view of the rapid and aggressive consequences frequently seen with this procedure. Patients require constant care to reduce complications and to contribute to the success of therapy. METHODS: In an attempt to ascertain the impact of systematic nutritional care on patients submitted to allogeneic hematopoietic stem cell transplantation, the present study assessed the nutritional and clinical status, use of parenteral nutrition, and complication and mortality rates in two groups of patients, who were submitted to transplantation between April 2003 and December 2004 (Non-intervention Group - NIG; n = 57) and between March 2006 and January 2008 (Intervention Group - IG; n = 34). RESULTS: There were no significant differences between groups in terms of clinical or nutritional profiles. Additionally, the length of hospital stay and complication and mortality rates were similar for both groups. However, time on parenteral nutrition during treatment was shorter for the IG [median 6.5 days (range: 1-28) for related donor recipients and 11 days (range: 1-21) for unrelated donor recipients] than for the NIG [median 20.5 days (range, 4-73) for patients submitted to myeloablative conditioning and 18.5 days (range: 11-59 days) for those submitted to nonablative conditioning]. CONCLUSION: The implementation of a nutritional follow-up and therapy protocol for adult patients submitted to hematopoietic stem cell transplantation shortens the duration of parenteral nutrition. It certainly has an impact on hospitalization costs and, potentially, on the rate of complications, even though this was not demonstrated in this study.